2009
DOI: 10.1097/aog.0b013e3181998bd1
|View full text |Cite
|
Sign up to set email alerts
|

Severe Separation of the Pubic Symphysis and Prompt Orthopedic Surgical Intervention

Abstract: Aggressive treatment of severe pubic symphysis separation with external fixation resulted in early ability to ambulate, void, and care for self and baby.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 5 publications
1
33
0
12
Order By: Relevance
“…Three articles were case series [3,18,21], the rest were reports of single cases [9,10,11,15,16,17,19,20,22,23]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three articles were case series [3,18,21], the rest were reports of single cases [9,10,11,15,16,17,19,20,22,23]. …”
Section: Resultsmentioning
confidence: 99%
“…Thus, 13 articles [3,9,10,11,15,16,17,18,19,20,21,22,23] met the inclusion criteria and were analyzed in detail (table 1). Three articles were case series [3,18,21], the rest were reports of single cases [9,10,11,15,16,17,19,20,22,23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present systematic review found use of physiotherapy as the main component of conservative treatment for the majority of women with SPD [1,4,7,10,12,[18][19][20][21]24,[27][28]. Most of the studies employed physiotherapy for walking reeducation, mobilization under supervision, and/or strengthening the core muscles, although only two studies detailed the stabilizing and/or strengthening exercises [10,15].…”
Section: Discussionmentioning
confidence: 99%
“…Failure includes: inadequate reduction, recurrent diastasis or persistent symptoms. 11,13,15 Surgical fixation of severe symphysis separation allows for earlier ambulation and ability to care for self and baby. 15 Injuries require 6-12 weeks to heal; we mobilised our patient at four weeks post-surgery as she was painfree and her social circumstances as well high risk for thrombosis necessitated earlier mobilisation.…”
Section: Introductionmentioning
confidence: 99%